KKN Tematik: Pencegahan dan penanganan Covid-19 untuk membentuk kepedulian masyarakat - Ayu Lestari Perdana; Haris Tehuayo; Suharni Suharni (KONSTELASI: Konvergensi Teknologi dan Sistem Informasi, 2021)
Corona Virus Disease 2019 (Covid-19) is increasingly becoming epidemic in Indonesia. One of the parties with great potential to assist the government in preventing and handling Covid-19 is universities. Universitas Islam Makassar, which is part of the academic community, also plays an active role in efforts to prevent and handle Covid-19, especially educating the public in the form of Thematic KKN. The Thematic KKN of Universitas Islam (UIM) in 2020 implemented in 20 districts /cities in South Sulawesi and in 6 other provinces, for 40 days in groups and individuals. One of the places that became the object of research was in the Maloku, Ujung Pandang District, Makassar City. The purpose of this activity is to support and strengthen the prevention and handling program for Covid-19 carried out by the government, most importantly educating the public about the dangers of Covid-19 and living a new life in the new normal era. The implementation of activities is carried out with a promotive, preventive and additional approach. Promotives are the promotion of clean and healthy living behaviors, and adhere to health protocols. Preventive, namely prevention of transmission by minimizing contact and avoiding crowds, while additional activities are programs deemed necessary and relevant, such as guidance and teaching of TPA students, cleaning around mosques and social services at the Maluko village head office. The results of this service activity received a positive response from both the government and the local community who felt the presence of students during KKN.Keywords: Prevention; Covid-19; KKN; Maloku.